Iatrogenic Cushing's syndrome after topical steroid therapy for psoriasis - Birsen Sahip; Mehmet Celik; Semra Ayturk; Ahmet Kucukarda; Onur Mert; Nejla Dincer; Sibel Guldiken; Armagan Tugrul (Wolters Kluwer Medknow Publications, 2016)
Glucocorticoids are used for the treatment of many diseases, such as inflammatory, allergic, autoimmune, and neoplastic diseases. They can be used in the form of topical, oral, inhalable, rectal, and intra-articular agents. Many topical steroid-related iatrogenic Cushing's syndrome cases affecting especially children have been reported in the literature. Topical steroid-related Cushing's syndrome is rarely seen in adults. In this report, we present the case of a 32-year-old male patient with iatrogenic Cushing's syndrome related to long-term clobetasol propionate treatment for psoriasis. In the context of such treatment, the glucocorticoid withdrawal problem has to be overcome. At present there is no consensus on steroid withdrawal. Patients on long-term glucocorticoid treatment must be evaluated for potential adverse effects and withdrawal symptoms by their physician and their endocrinologist.